Jalinan Cinta dan Keadilan - Mulyatno, C.B. (Jurnal Orientasi Baru, 2007)
Industrialized society has been greatly driven by major economical and political powers. Science and technology, human resources, competition, social welfare, political participation and tolerance are widely discussed topics. Meanwhile